ANALISIS KESULITAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 14/I SUNGAI BAUNG DALAM PEMBELAJARAN BAHASA INDONESIA - Gusmiva, Adelsa; Masyitah, Ayu; Agil Zuhriana, Winda; Pangestuti, Diana; Khoirunnisa (STKIP Subang, 2026)
This study was motivated by the still-low reading comprehension skills of elementary school students, which hinder the achievement of literacy competencies. The study aims to describe the nature of reading comprehension difficulties, identify their causes, and examine teachers’ efforts to address them among fourth-grade students at SDN 14/I Sungai Baung. The study employed a descriptive qualitative approach, with data sources consisting of fourth-grade students and teachers. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis utilized an interactive model comprising data reduction, data presentation, and drawing conclusions. The results of the study indicate that the students’ main difficulties include understanding main ideas, the meaning of vocabulary, and drawing conclusions from texts. The contributing factors stem from both internal student factors and external learning factors. Teachers’ efforts were implemented through the use of contextual learning strategies and the provision of intensive reading practice. The findings also reveal that conventional teaching methods, limited learning media, and insufficient parental support at home are external factors that further exacerbate students' reading comprehension difficulties. These findings have important implications for the development of more effective reading learning strategies in elementary schools.